Pelatihan dan Sosialisasi Pembuatan Deterjen Cair Ramah Lingkungan Pengganti Deterjen Sintetik - Harfadli, Muhammad Ma'arij; Jordan, Nadia Almira; Ulimaz, Mega (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The dominance of the use of synthetic detergents is tends to be high, especially in RT 54 neighborhood Karang Joang Village, North Balikpapan. The use of packaged detergent that produce B3 waste is still unknown by the residents. In addition, the absence of waste management and particular disposal systems also contribute as a negative impact on the environment. The training and socialization activities for making environmentally friendly detergents were carried out to provide information about the basic ingredients for eco-friendly detergent using Methyl Ester Sulfonate (MES) as a vegetable surfactant, as well as to encourage participants to be able to make detergents independently. The method used in this activity is demonstrations by explaining the stages of manufacture. The process of making detergent is carried out through the preparation stage, the making process and recording in video, using simple tools and materials. Video demonstrations were published on social media so that the dissemination of information was wider than the initial target of the activity. Through this activity, the results obtained were that the stages of making detergents that were not too complicated, so it could be easily understood, especially with a video guide that could be accessed at any time.DOI: https://doi.org/10.26905/abdimas.v6i1.5025